Influence mechanism of carboxyl groups of fatty acids on the weak interaction of low-rank coal-water interface - Zechen LIU; Xianshu DONG; Yuping FAN; Yinfei LIAO; Yijun CAO (Meitan xuebao, 2025)
The effect of the number of carboxyl groups of fatty acids in the compound collector on the flotation mechanism of low-rank coal is still limited. Density functional theory (DFT) combined with Fourier infrared spectroscopy (FTIR) and Zeta potential was used to study the mechanism of the weak interaction between low-rank coal-water interface molecules and the compound collector composed of fatty acids (n-capric acid, sebacic acid) and dodecane, respectively. DFT calculation results show that the hydrogen bonding, charge transfer, and interaction energy between sebacic acid molecule with two carboxyl groups and benzoic acid/phenol/water molecule are stronger than that of the n-capric acid molecule with one carboxyl group, and the interaction between the sebacic acid molecule and water molecule is stronger than that between sebacic acid molecule and benzene/benzoic acid molecule. It shows that the interaction between carboxylic acid molecules with more carboxylic groups and the surface of low-rank coal is greatly affected by water. The results of FTIR and Zeta potential show that the number of carboxyl groups has little effect on the adsorption of the hydrophobic water level point of low-rank coal, and the hydrogen bond between the compound collector with two carboxyl groups and the low-rank coal is stronger, and the effect on the potential value of the coal sample surface is small, indicating that the hydrogen bond between carboxyl groups and water molecules of some sebacic acid molecules leads to less adsorption of the compound collector containing sebacic acid on the surface of low-rank coal. At the same time, the compound collector containing sebacic acid can obtain lower ash content of clean coal, but sacrifice more clean coal yield, while the compound collector containing n-capric acid has both collector performance and better selectivity. It shows that in the actual flotation process, the strong hydrogen bond and the electrostatic interaction between sebacic acid and water weaken the collection performance of its compound collector for low-rank coal, which also confirms the research results of DFT, FTIR, and Zeta.